Competitividad en el cantón Latacunga - Venegas Valverde, Jorge Antonio (2023)
The present investigation determined the competitiveness index in the Latacunga canton, in order to know the current situation in terms of business and social well-being in the city of Latacunga. The index contains several components that allow reflecting the state of the canton, such as: economic-business, socio-demographic, institutional, infrastructure and environmental. The economic-business component has several indicators and variables that evaluate the canton on issues related to the number of companies, exports, economically active population, etc. The socio-demographic component shows, on the other hand, indicators related to demography, education and security. The institutional component focuses on obtaining data that evaluates the municipal management of the canton.